Relationship Between Heterodera schachtii, Meloidogyne hapla, and Nacobbus aberrans on Sugarbeet - Inserra, R N (Journal of nematology, 1984)
Heterodera schachtii, Meloidogyne hapla, and Nacobbus aberrans either alone, or in various combinations with each other, can, when inoculated at a concentration of 12 second-stage juveniles/ cm(3) of soil, cause a significant (P = 0.01) suppression of growth of sugarbeet (cv. Tasco AH14) seedlings. M. hapla and H. schachtii decreased growth of sugarbeet more than N. aberrans over a 60-day period. The adverse effect of N. aberrans on the final population/initial population (Pf/Pi) ratio for either M. hapla or H. schachtii was dependent on time, and was more accentuated on that of M. hapla than on that of H. schachtii. Neither M. hapla nor H. schachtii had an adverse effect on the Pf/ Pi ratio of N. aberrans. N. aberrans is considered to be less aggressive on sugarbeet than either H. schachtii or M. hapla. Sections of sugarbeet roots infected simultaneously with H. schachtii and N. aberrans showed scattered vascular elements between the N. aberrans syncytium located in the central part of the root and that of H. schachtii in the peripheral position